Hubungan Profil Klinikopatologik dengan Rekurensi Karsinoma Payudara Invasif di Departemen Patologi Anatomik FKUI/RSCM - Ineke Anggreani; Primariadewi Rustamadji (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2022)
ABSTRACTBackgroundBreast cancer is the most common malignancy and the leading cause of death in women. Invasive breast carcinoma is a breastmalignancy originating from the glandular epithelium of the breast. Approximately 40% of invasive breast carcinomas had recur.There are several factors that influence the occurrence of recurrence, such as age, tumor size, lymphovascular invasion, incisionmargins, hormonal status and therapy. This study aims to determine the clinicopathological profile associated with recurrence 5years after therapy for invasive breast carcinoma.MethodsThis study is a retrospective study with data collection carried out through the archives of the Department of Anatomical Pathology,Faculty of Medicine, University of Indonesia, Dr. Cipto Mangunkusumo General Hospital within a period of 2 years (2014-2015). Theclinicopathological data was searched for up to 5 years of therapy.ResultsFrom the 54 cases of invasive breast carcinoma in this study, all were women with mean age 48.3 years. A total of 18 cases(33.3%) experienced recurrence, especially in patients aged ≤50 years, tumor mass size more than 2 cm and luminal B moleculartype. Tumor margin is difficult to evaluate because many review cases do not submit the tumor margin section. Therapy received bypatients was in accordance with standard procedures’ hospital, both neoadjuvant and adjuvant chemotherapy. From the statisticalanalysis, there was no significant relation between all profiles that studied with recurrence. It is because the comparison of numberof recurrent and non-recurrent cases is not equal.ConclusionOne third of advanced invasive breast carcinomas treated with neoadjuvant and showing a partial response have recurrence,whereas no complete response has recurrence. Tumor size, histologic grade, molecular type and adherence to routine follow-uptreatment influenced the recurrence within 5 years of treatment.